Songs 4 worship shout to the Lord ; open the eyes of my heart - Integrity, Inc.; Time-Life Video (Mobile, AL : Integrity, Inc. : Time-Life Video, 2002)
Celebrate the Lord and enter God's presence with song. Join with thousands of Christians around the world in glorifying the name of Jesus.
Open the eyes of my heart: All things are possible / featuring Darlene Zschech -- Trading my sorrows / featuring the Women of Faith Worship Team from Integrity Music -- I see the Lord / featuring Ron Kenoly -- Jesus lover of my soul / featuring Darlene Zschech -- God will make a way / featuring Don Moen -- I worship you almight God / featuring Don Moen -- We will glorify / featuring Twila Paris -- Oh the glory of His presence / featuring Ron Kenoly -- To Him who sits on the throne / featuring Don Moen -- Open the eyes of my heart / featuring the Women of Faith Worship Team from Integrity Music.
Container and disc date may vary ; container and disc state color and b&w but film is color.
Various performers.
Originally released, 2001.
DVD.
Keywords: Contemporary Christian music